19.6k views
0 votes

2 (3)/(5) - 1 (3)/(8)


1 Answer

5 votes

let's firstly convert the mixed fractions to improper fractions, and then subtract.


\bf \stackrel{mixed}{2(3)/(5)}\implies \cfrac{2\cdot 5+3}{5}\implies \stackrel{improper}{\cfrac{13}{5}}~\hfill \stackrel{mixed}{1(3)/(8)}\implies \cfrac{1\cdot 8+3}{8}\implies \stackrel{improper}{\cfrac{11}{8}} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{13}{5}-\cfrac{11}{8}\implies \stackrel{\textit{using the LCD of 40}}{\cfrac{(8)13~~-~~(5)11}{40}}\implies \cfrac{104-55}{40}\implies \cfrac{49}{40}\implies 1(9)/(40)

User Mplungjan
by
4.7k points